PEMBERDAYAAN ANAK JALANAN MELALUI KEGIATAN TALENT SCOUTING - Nadya Nadya; Rina Marlina; Uum Suminar (Jurnal Pendidikan Sepanjang Hayat, 2022)
Empowerment is related to a process of giving power or strength to someone who is considered weak which aims to create individuals who are more advanced, independent and can fulfill their life needs to become more prosperous individuals physically and mentally. This study aims to describe one of the activities contained in the Cahaya Anak Negeri Community, namely Talent Scouting as a form of empowerment for street children. This research uses a qualitative approach with a descriptive type of research. data collection techniques in the form of observation, interviews and documentation. The research subjects consisted of two coaches, two Talent Scouting tutors and two street children who were involved in Talent Scouting activities. The results of the study revealed that the empowerment provided by the Cahaya Anak Negeri Community through Taleng Scouting activities brought significant changes to the lives of street children who were members.